Effect of Gastrointestinal Microbiota and Probiotics/Prebiotics in the Diet on the Development of Alzheimer’s Disease – A Comprehensive Review - Francuziak, Anna Ewelina; Dembicki, Piotr Mikołaj; Kozłowska, Kinga; Książek, Tomasz Karol; Szeliga, Aleksandra; Borowski, Maciej; Dzieszko, Natalia; Szczepański, Michał; Kalinowska, Weronika; Kulasza, Paulina Sara (Quality in Sport, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by memory loss, cognitive decline, and behavioral changes, affecting over 50 million people worldwide. Its etiology involves complex genetic and environmental factors, and recent evidence implicates the gut–brain axis in disease progression. Dysbiosis of the gastrointestinal microbiota has been linked to increased neuroinflammation and accumulation of amyloid-β (Aβ) plaques and neurofibrillary tau tangles, the hallmark pathologies of AD. Conversely, beneficial gut bacteria produce metabolites (such as short-chain fatty acids, SCFAs) that may counteract these processes. This review summarizes current knowledge on how dietary interventions (probiotics and prebiotics) modulate the gut microbiota and influence AD pathology. Studies indicate that probiotic strains (notably Lactobacillus and Bifidobacterium) and prebiotics have potential to improve cognitive function and reduce neuroinflammation in preclinical and clinical settings. However, studies vary in design and scale, and therapeutic protocols are not yet standardized. Further research is needed to establish efficacy, dosage, and safety of microbiota-targeted interventions. Modulating the gut microbiota thus represents a novel avenue for AD prevention and treatment, although conclusive clinical evidence is still emerging.